Ultralight high-strength high-plastic-deformation magnesium-lithium alloy and preparation method and application thereof
By regulating the element composition and process of magnesium lithium alloy, ultralight, high strength, high plastic deformation magnesium lithium alloy was prepared, which solved the problem of difficulty in balancing strength, plasticity and density, and realized the industrial application of high-performance magnesium lithium alloys.
Patent Information
- Application Number
- CN202510645853.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-08-01
AI Technical Summary
The existing deformed magnesium lithium alloys are difficult to balance strength, plasticity and density, and have poor processing performance, which leads to prone to cracking during processing and low yield, limiting their application in aerospace, military and 3C electronics fields.
By accurately controlling the composition and ratio of alloying elements, ultra-light, high strength, and high plastic deformation magnesium lithium alloys are prepared, including Li, La, Ce, Al, Zn, Mn, Sr, Y and other elements. Combined with smelting, homogenizing heat treatment and hot extrusion processes, the phase structure and strengthening mechanism of the alloy are optimized to ensure the lightweight and high performance of the alloy.
It has achieved lightweighting of magnesium lithium alloys, with a density of 1.38~1.59g/cm3, a tensile strength of ≥284MPa, a yield strength of ≥203MPa, and an elongation of 17~35%, meeting the high performance requirements of aerospace, military industry and 3C electronics fields, reducing production costs.
Smart Images

Figure CN120400638A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloys, and particularly relates to an ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, a preparation method thereof, and an application thereof. Background Art
[0002] As one of the lightest metal structural materials, magnesium-lithium alloys have great application potential in the fields of aerospace, military, 3C electronics, etc. due to their advantages such as low density and high specific strength. The density of magnesium-lithium alloys is between that of magnesium and lithium, and theoretically, they can effectively replace some traditional metal materials. For example, in the aerospace field, using magnesium-lithium alloys to manufacture key components such as the wings and fuselage frames of aircraft can significantly reduce the weight while ensuring the structural strength; in the electronic device industry, magnesium-lithium alloys can be used to manufacture the casings of mobile phones, tablet computers, etc., helping to make the products thinner and lighter. At the same time, their good electromagnetic shielding performance can also protect the internal precision electronic components.
[0003] However, there are still many problems with current deformed magnesium-lithium alloys. On the one hand, it is still difficult to balance the strength, plasticity, and density of magnesium-lithium alloys; when pursuing extremely low density, their crystal structure and internal tissue characteristics make it difficult for their strength and plasticity to meet the usage requirements of key structural components, and they are extremely prone to failure when subjected to large external forces or complex stresses. On the other hand, the processing performance is poor. Due to their special physical and chemical properties, they are extremely prone to work hardening during the processing process. For example, they are prone to cracking during forging and rolling, resulting in a low finished product rate and high production costs, which to a certain extent limits their popularization and application.
[0004] Therefore, it is very urgent to develop a deformed magnesium-lithium alloy with simple preparation process and low cost, which has important significance for the popularization and application of magnesium alloys. Summary of the Invention
[0005] To solve the above technical problems, the present invention proposes an ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, a preparation method thereof, and an application thereof. The preparation process of the present invention is simple and efficient. On the premise of ensuring the lightweight of the magnesium-lithium alloy, by precisely controlling the composition and ratio of alloying elements, a significant improvement in its mechanical properties is achieved. This breakthrough result shows important application value in high-end manufacturing fields such as aerospace, national defense, and 3C electronics.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] The present invention provides an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, which, by mass percentage, comprises the following components: Li 7.0-15.0%, La 0.01-1.8%, Ce 0.01-2.5%, Al 1.0-7.0%, Zn 0.5-3.0%, Mn 0.15-0.4%, Sr 0.01-0.05%, Y 0.01-0.05%, Fe ≤ 0.05%, Ni ≤ 0.005% and Cu ≤ 0.05%, and the balance is Mg and inevitable impurities.
[0009] The density of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy of the present invention is only 1.38-1.59 g / cm 3 , the tensile strength ≥ 284 MPa, the yield strength ≥ 203 MPa, and the elongation is 17-35%.
[0010] Further, the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, by mass percentage, comprises the following components: Li 11.0-15.0%, La 0.8-1.7%, Ce 1.0-2.1%, Al 4.3-7.0%, Zn 0.9-2.2%, Mn 0.2-0.4%, Sr 0.02-0.05%, Y 0.02-0.04%, Fe ≤ 0.05%, Ni ≤ 0.005% and Cu ≤ 0.05%, and the balance is Mg and inevitable impurities.
[0011] Furthermore, the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, by mass percentage, comprises the following components: Li 12.0-15.0%, La 0.8-1.5%, Ce 1.0-2.1%, Al 4.3-7.0%, Zn 0.9-2.2%, Mn 0.2-0.3%, Sr 0.02-0.03%, Y 0.02-0.04%, Fe ≤ 0.05%, Ni ≤ 0.005% and Cu ≤ 0.05%, and the balance is Mg and inevitable impurities.
[0012] The second technical solution of the present invention:
[0013] The present invention also provides a preparation method of the above ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, which comprises the following steps: weighing raw materials according to mass percentage, then melting the raw materials, and after the melting is completed, casting to obtain a magnesium-lithium alloy ingot; sequentially performing homogenization heat treatment and hot extrusion on the magnesium-lithium alloy ingot to obtain the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy;
[0014] The temperature of the smelting is 690 - 750 °C, and the time of the smelting is 30 - 60 min. If the smelting temperature is too high, the Li element will volatilize violently, and it may cause the coarsening of the primary phase, reducing the strength and elongation of the material. If the smelting temperature is too low, the relative viscosity of the melt is high, the diffusion of alloying elements is slow, and composition segregation (such as Li enrichment area, rare earth aggregation) is likely to occur, resulting in defects such as uneven mechanical properties. If the smelting time is too short, the element diffusion is insufficient, and the elements cannot be completely dissolved, resulting in undissolved particles at the grain boundaries, causing stress concentration and other phenomena, reducing the strength and plasticity of the alloy. If the smelting time is too long, the Li element in the melt volatilizes severely, the proportion of the β phase decreases, and the primary phase coarsens, reducing the performance of the material.
[0015] Further, the raw materials include pure lithium, pure magnesium, magnesium - lanthanum master alloy, magnesium - cerium master alloy, pure aluminum, pure zinc, anhydrous manganese chloride, metallic strontium, and magnesium - yttrium master alloy.
[0016] Exemplarily, the magnesium - lanthanum master alloy is magnesium - lanthanum 30 master alloy; the magnesium - cerium master alloy is magnesium - cerium 30 master alloy; the magnesium - yttrium master alloy is magnesium - yttrium 30 master alloy.
[0017] Further, after the smelting is completed, it is cooled and left standing before casting.
[0018] Further, the cooling and standing is to cool to a temperature of 670 ± 1 °C and stand for 10 - 20 min.
[0019] Exemplarily, the preparation steps of the magnesium - lithium alloy ingot are as follows: Weigh the raw materials (pure magnesium, magnesium - lanthanum master alloy, magnesium - cerium master alloy, pure aluminum, pure zinc, anhydrous manganese chloride, metallic strontium, and magnesium - yttrium master alloy) according to the mass percentage, then add the raw materials into a vacuum melting furnace, evacuate the air, then fill it with argon, heat up to 690 - 750 °C for smelting for 30 - 60 min, cool and stand for 10 - 20 min, and cast to obtain the magnesium - lithium alloy ingot.
[0020] Further, the temperature of the homogenization heat treatment is 350 - 380 °C, and the time of the homogenization heat treatment is 4 - 6 h.
[0021] Further, during the hot extrusion: the temperature of the ingot is 210 - 250 °C, the extrusion rate is 3.0 - 5.0 mm / s, and the extrusion ratio is 20∶1.
[0022] The third technical solution of the present invention:
[0023] The present invention also provides the application of the above - mentioned ultra - light, high - strength, and high - plasticity - deformed magnesium - lithium alloy in the fields of 3C electronics, military equipment, or aerospace.
[0024] Exemplarily, the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy of the present invention can be used to prepare the wings, fuselage frames of aircraft, satellite honeycomb sandwich parts, etc., and can also be used to prepare the casings of mobile phones, tablet computers, etc.
[0025] Compared with traditional magnesium-lithium alloys, the present invention effectively regulates the alloy composition. By defining the content ranges of the main elements Li, Al, and Zn, the phase structure and strengthening mechanism of the alloy are optimized. In addition, by adding alloying elements such as La, Ce, Sr, and Y, a synergistic strengthening effect is achieved. On the premise of ensuring the light weight of the magnesium-lithium alloy, the comprehensive performance of the magnesium-lithium alloy is improved through microalloying.
[0026] During the melting process, to prevent the burning loss of Li element at high temperatures, the present invention obtains a magnesium-lithium alloy with uniform structure and excellent performance by regulating parameters such as temperature and time under inert gas protection. The density of the deformed magnesium-lithium alloy is 1.38 - 1.59 g / cm 3 , the tensile strength ≥ 284 MPa, the yield strength ≥ 203 MPa, and the elongation is 17 - 35%, meeting the strict requirements of the aerospace, military, and 3C electronics fields for high-performance and lightweight materials, and providing strong support for the wide application of magnesium-lithium alloys.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] The present invention provides an ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy. By regulating elements such as Li, La, Ce, Al, Zn, Mn, Sr, and Y, while ensuring the light weight of the magnesium-lithium alloy, the performance of the magnesium-lithium alloy is improved. The density of the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy of the present invention is only 1.38 - 1.59 g / cm 3 , the tensile strength ≥ 284 MPa, the yield strength ≥ 203 MPa, and the elongation is 17 - 35%. Its preparation method is simple, the process stability is good, and it can be industrially produced, having broad application prospects in the aerospace, military equipment, and 3C electronics fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention. In the drawings:
[0030] Figure 1 is the process flow chart for the preparation of the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy of the present invention;
[0031] Figure 2 is the phase diagram of the magnesium-lithium alloy. DETAILED DESCRIPTION OF THE INVENTION
[0032] The various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and implementation manners of the present invention.
[0033] It should be understood that the terms used in the present invention are only for describing specific embodiments and are not intended to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the said documents. In case of conflict with any incorporated document, the content of this specification shall prevail.
[0035] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific embodiments of the present invention specification, which are obvious to those skilled in the art. Other embodiments obtained from the specification of the present invention are obvious to those skilled in the art. The specification and examples of the present invention are merely exemplary.
[0036] Regarding the use of "comprising", "including", "having", "containing", etc. in this article, they are all open-ended terms, meaning including but not limited to.
[0037] In the present invention, "3C electronics" refers to three major technology products: computers, communications, and consumer electronics.
[0038] The embodiments of the present invention provide a super-light, high-strength, and high-plasticity deformable magnesium-lithium alloy, which, by mass percentage, comprises the following components: Li 7.0 - 15.0%, La 0.01 - 1.8%, Ce 0.01 - 2.5%, Al 1.0 - 7.0%, Zn 0.5 - 3.0%, Mn 0.15 - 0.4%, Sr 0.01 - 0.05%, Y 0.01 - 0.05%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and inevitable impurities.
[0039] The super-light, high-strength, and high-plasticity deformable magnesium-lithium alloy provided by the present invention has a density of only 1.38 - 1.59 g / cm3 , the tensile strength ≥ 284 MPa, the yield strength ≥ 203 MPa, and the elongation is 17 - 35%.
[0040] In some preferred embodiments of the present invention, the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, by mass percentage, comprises the following components: Li 11.0 - 15.0%, La 0.8 - 1.7%, Ce 1.0 - 2.1%, Al 4.3 - 7.0%, Zn 0.9 - 2.2%, Mn 0.2 - 0.4%, Sr 0.02 - 0.05%, Y 0.02 - 0.04%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and unavoidable impurities.
[0041] In some preferred embodiments of the present invention, the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, by mass percentage, comprises the following components: Li 12.0 - 15.0%, La 0.8 - 1.5%, Ce 1.0 - 2.1%, Al 4.3 - 7.0%, Zn 0.9 - 2.2%, Mn 0.2 - 0.3%, Sr 0.02 - 0.03%, Y 0.02 - 0.04%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and unavoidable impurities.
[0042] The embodiments of the present invention further provide a preparation method of the above-mentioned ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy. The process flow chart of the preparation process is as Figure 1 shown, and it comprises the following steps: weighing the raw materials according to the mass percentage, then melting the raw materials, cooling and standing after the melting is completed, and then casting to obtain a magnesium-lithium alloy ingot; sequentially performing homogenization heat treatment and hot extrusion on the magnesium-lithium alloy ingot to obtain the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy;
[0043] The temperature of the melting is 690 - 750 °C, and the time of the melting is 30 - 60 min.
[0044] In the embodiments of the present invention, preferably, the temperature of the melting is 690 - 725 °C, and the time of the melting is 30 - 50 min.
[0045] In some embodiments of the present invention, the raw materials include pure lithium, pure magnesium, magnesium-lanthanum master alloy, magnesium-cerium master alloy, pure aluminum, pure zinc, anhydrous manganese chloride, metallic strontium, and magnesium-yttrium master alloy. Exemplarily, the magnesium-lanthanum master alloy is magnesium-lanthanum 30 master alloy; the magnesium-cerium master alloy is magnesium-cerium 30 master alloy; the magnesium-yttrium master alloy is magnesium-yttrium 30 master alloy. The pure magnesium is a magnesium ingot (purity 99.99%); the pure aluminum is an aluminum ingot (purity 99.99%); the pure zinc is a zinc ingot (purity 99.99%); the purity of anhydrous manganese chloride is 99%; the purity of metallic strontium is 99%; the purity of pure lithium is 99.99%. By selecting the raw materials, Fe≤0.05wt%, Ni≤0.005wt%, and Cu≤0.05wt% are controlled in the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy.
[0046] In some embodiments of the present invention, after the melting is completed, the temperature is decreased and the alloy is allowed to stand still until the temperature reaches 670±1°C, and it is allowed to stand for 10 - 20 minutes.
[0047] In some embodiments of the present invention, the temperature of the homogenization heat treatment is 350 - 380°C, and the time of the homogenization heat treatment is 4 - 6 hours.
[0048] In some embodiments of the present invention, during hot extrusion: the temperature of the cast rod is 210 - 250°C, the extrusion rate is 3.0 - 5.0 mm / s, and the extrusion ratio is 20∶1.
[0049] The ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy prepared in the embodiments of the present invention can be used in the fields of 3C electronics, military equipment, or aerospace. Exemplarily, the ultra-light, high-strength, and high-plasticity deformed magnesium-lithium alloy of the present invention can be used to prepare the wings, fuselage frames, satellite honeycomb sandwich parts, etc. of aircraft, and can also be used to prepare the casings of mobile phones, tablet computers, etc.
[0050] The principle of the present invention:
[0051] In the magnesium-lithium alloy system of the present invention, Li is the core main element, and its unique physical and chemical properties play a decisive role in the alloy properties. The density of the Li element is relatively low. When it is added to the Mg matrix at a mass percentage of 7.0 - 15.0%, to a certain extent, it changes the crystal structure of the magnesium alloy. Combining with the phase diagram (see Figure 2)It can be seen that with the change of Li content, it promotes the formation of α-Mg phase, α+β phase, and β-Li phase in the alloy. The β phase has a body-centered cubic (bcc) structure. Compared with the hexagonal close-packed (hcp) structure of Mg, the bcc structure has more slip systems. According to the dislocation theory of crystal plastic deformation, the increase in slip systems provides more paths for dislocation slip when the alloy is stressed. This not only effectively reduces the overall density of the magnesium-lithium alloy and achieves the goal of lightweight, but also creates a microstructural basis for the improvement of the plasticity of the magnesium-lithium alloy. During the deformation process, the existence of multiple slip systems makes the dislocation interaction more complex and promotes the work-hardening effect. The intersection and entanglement of dislocations between different slip systems increase the resistance to dislocation movement, thereby improving the strength of the magnesium-lithium alloy to a certain extent.
[0052] During the solidification process of the magnesium-lithium alloy, La and Ce atoms can act as heterogeneous nucleation cores. The existence of this heterogeneous nucleation core significantly reduces the energy required for nucleation, greatly increases the nucleation rate of the magnesium-lithium alloy, and then achieves the effect of grain refinement on the microstructure of the magnesium-lithium alloy, thereby increasing the grain boundary area. According to the Hall-Petch formula, the increase in the number of grain boundaries can effectively hinder the slip of dislocations, thus improving the strength of the magnesium-lithium alloy. At the same time, the increase in the number of grain boundaries enables the magnesium-lithium alloy to better coordinate the plastic deformation between adjacent grains during the plastic deformation process, enhancing the toughness of the magnesium-lithium alloy.
[0053] In addition, La and Ce can also react chemically with other alloying elements to form stable high-melting-point compounds. These compounds are dispersed during the solidification process of the magnesium-lithium alloy, reducing the segregation of impurity elements at the grain boundaries and avoiding the destruction of the matrix continuity by impurities, further enhancing the stability of the alloy microstructure.
[0054] Al and Zn mainly improve the strength of the alloy through the solid-solution strengthening mechanism in the alloy. There are differences in their radii from the Mg atomic radius. When they are solid-solved in the Mg matrix, it will cause lattice distortion in the alloy. When dislocations move in the crystal, they need to overcome various resistances. The elastic stress field caused by solute atoms is one of the resistances, hindering the movement of dislocations, and thus improving the strength and hardness of the magnesium alloy. By controlling the contents of Al (1.0 - 7.0 wt%) and Zn (0.5 - 3.0 wt%), while ensuring the solid-solution strengthening effect, it can effectively avoid excessive lattice distortion caused by over-solid solution, and thus prevent a significant decrease in the plasticity of the alloy.
[0055] During the solidification of the alloy, Mn atoms can act as inhibitors for the growth of crystal nuclei, inhibiting the growth of grains and thus refining the grain structure. From the perspective of corrosion electrochemistry, Mn can form a dense oxide film rich in MnO on the alloy surface. This oxide film has good chemical stability and electronic insulation, and can effectively prevent the direct contact between the corrosion medium and the alloy matrix, improving the corrosion resistance of the alloy. It has a strong affinity for impurity elements (such as Fe, Ni, etc.), can form insoluble compounds, reduce the segregation of harmful impurities at grain boundaries, reduce the tendency of galvanic corrosion, and improve the corrosion resistance of magnesium alloys.
[0056] According to the interface energy theory, Sr and Y atoms will preferentially segregate at grain boundaries and phase boundaries, reducing the interface energy, inhibiting the growth of grains and the coarsening of phases, changing the distribution and morphology of phases in the alloy, and having a good modification effect on magnesium alloys, making their microstructure more uniform.
[0057] Metal cation Fe 2+ 、Ni 2+ 、Cu 2+ The standard electrode potentials of ( - 0.44V, - 0.24V, and + 0.34V respectively) are significantly higher than that of magnesium ( - 2.363V). In the alloy, cathode phases (such as intermetallic compounds like FeMg2, NiMg2, CuMg2, etc.) will be formed, constituting a microcell with the magnesium matrix. The cathode phase acts as the positive electrode of the corrosion cell, promoting the accelerated dissolution of the magnesium matrix (anode). Especially in corrosive media containing Cl - ions, the corrosion rate can be increased several times. Therefore, in this invention, Fe≤0.05wt%, Ni≤0.005wt%, and Cu≤0.05wt% are strictly controlled.
[0058] Keep the magnesium - lithium alloy casting rod at a temperature range of 350 - 380°C for 4 - 6 hours for homogenization heat treatment. The alloy atoms in the magnesium - alloy casting rod obtain a certain amount of thermal activation energy, and solute atoms diffuse from high - concentration regions to low - concentration regions, eliminating defects such as composition segregation and dendritic coarsening in the casting rod to a certain extent, making the composition and microstructure of the magnesium - lithium alloy evenly distributed. If the homogenization temperature is too low, the solute cannot be fully diffused, which may lead to still existing composition segregation in the magnesium - lithium alloy matrix, incomplete elimination of residual stress, and defects such as coarse secondary phases, thus affecting the subsequent extrusion performance; if the homogenization temperature is too high, it may lead to defects such as grain growth, alloy element burning loss, over - burning of the matrix structure, and increased energy consumption, which will have an adverse impact on the mechanical properties of the magnesium - lithium alloy.
[0059] During the subsequent hot extrusion process, the temperature of the magnesium-lithium alloy casting rod is controlled at 210 - 250 °C, the extrusion rate is 3.0 - 5.0 mm / s, and the extrusion ratio is 20:1. Under the hot state conditions of hot extrusion, the thermal movement of alloy atoms in the magnesium-lithium alloy casting rod intensifies, and the movement ability of dislocations increases, resulting in a significant improvement in the plasticity of the alloy. During the extrusion process, the alloy undergoes a certain amount of plastic deformation, and a large number of dislocations are generated and move inside the crystal. At the same time, the effect of the extrusion ratio causes the grains of the alloy to be elongated along the extrusion direction, forming a fibrous structure. During this process, dynamic recrystallization also occurs, which not only improves the strength of the alloy but also enhances the plasticity and toughness of the alloy, enabling the alloy to finally possess excellent comprehensive properties of ultra-light weight, high strength, and high plasticity. If the hot extrusion temperature is too low, the extrusion resistance of the material increases, the metal fluidity is poor, and the atomic diffusion ability of the alloy at low temperature is weak. During the extrusion process, the deformation non-uniformity increases, resulting in an unsatisfactory effect of tissue refinement and prone to the situation of local tissue coarsening. If the hot extrusion temperature is too high, it may lead to defects such as a decrease in the surface quality of the deformed magnesium-lithium alloy, overburning of the structure, and grain growth, ultimately resulting in problems such as low and unstable mechanical properties of the deformed magnesium-lithium alloy.
[0060] Unless otherwise specified, the room temperature in the present invention is calculated as 25 ± 2 °C.
[0061] All raw materials used in the examples of the present invention are obtained through commercial purchases. As an example, the magnesium-lanthanum 30 master alloy is purchased from Suzhou Rongqian Rare Metal Products Co., Ltd., with the brand name of magnesium-lanthanum 30; the magnesium-cerium 30 master alloy is purchased from Suzhou Chuanmao Metal Materials Co., Ltd., with the brand name of MgCe30; the magnesium-yttrium 30 master alloy is purchased from Suzhou Chuanmao Metal Materials Co., Ltd., with the brand name of MgY30.
[0062] It should be noted that the details not described in the present invention are all conventional operation means in the art and are not the focus of the present invention. For example, the specific method of casting is completed by using a conventional casting method.
[0063] The technical solutions of the present invention will be further described below through examples.
[0064] Example 1
[0065] This example provides a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components in mass percentage: Li 8.0%, La 1.0%, Ce 2.0%, Al 3.0%, Zn 1.0%, Mn 0.2%, Sr 0.03%, Y 0.03%, Fe ≤ 0.05 wt%, Ni ≤ 0.005 wt%, and Cu ≤ 0.05 wt%, with the balance being Mg and unavoidable impurities.
[0066] The specific steps of the above-mentioned super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy are as follows:
[0067] Accurately weigh the above-mentioned raw materials (magnesium ingot, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingot, zinc ingot, anhydrous manganese chloride, metallic strontium, and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate the air, and refill with argon. Wait until the temperature rises to 720±1°C and melt for 40 minutes, then cool down to 670±1°C, stand for 20 minutes, and finally cast into a magnesium-lithium alloy ingot;
[0068] Heat treat the as-cast magnesium-lithium alloy ingot at 350±1°C for 4 hours for homogenization heat treatment;
[0069] Hot extrude the homogenized magnesium-lithium alloy ingot. The extrusion parameters are: the temperature of the ingot is 230±1°C, the extrusion rate is 3.0 mm / s, and the extrusion ratio is 20∶1. Finally, a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is obtained.
[0070] Refer to "GB / T 16865-2023 Test Specimens and Methods for Tensile Testing of Wrought Aluminum, Magnesium and Their Alloys" for performance testing. In this example, the density of the super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is 1.59 g / cm 3 , the tensile strength is 284.04 MPa, the yield strength is 203.3 MPa, and the elongation is 17.5% (see Table 1 for details).
[0071] Example 2
[0072] This example provides a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, which consists of the following components by mass percentage: Li 9.0%, La 0.5%, Ce 1.5%, Al 6.0%, Zn 1.2%, Mn 0.25%, Sr 0.05%, Y 0.02%, Fe≤0.05 wt%, Ni≤0.005 wt%, and Cu≤0.05 wt%. The balance is Mg and unavoidable impurities.
[0073] The specific steps of the above-mentioned super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy are as follows:
[0074] Accurately weigh the above-mentioned raw materials (magnesium ingot, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingot, zinc ingot, anhydrous manganese chloride, metallic strontium, and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate the air, and refill with argon. Wait until the temperature rises to 730±1°C and melt for 50 minutes, then cool down to 670±1°C, stand for 15 minutes, and finally cast into a magnesium-lithium alloy ingot.
[0075] Heat treat the as-cast magnesium-lithium alloy ingot at 360±1°C for 5 hours for homogenization heat treatment.
[0076] The homogenized magnesium-lithium alloy cast rod is subjected to hot extrusion. The extrusion parameters are as follows: the temperature of the cast rod is 230 ± 1 °C, the extrusion rate is 5.0 mm / s, and the extrusion ratio is 20:1. Finally, a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is obtained.
[0077] The performance testing method is the same as that in Example 1. In this example, the density of the super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is 1.58 g / cm 3 , the tensile strength is 316.13 MPa, the yield strength is 212.7 MPa, and the elongation is 18.7% (see Table 1 for details).
[0078] Example 3
[0079] This example provides a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components by mass percentage: Li 11%, La 1.7%, Ce 1.6%, Al 5.5%, Zn 1.5%, Mn 0.33%, Sr 0.04%, Y 0.03%, Fe ≤ 0.05 wt%, Ni ≤ 0.005 wt%, and Cu ≤ 0.05 wt%. The balance is Mg and unavoidable impurities.
[0080] The specific steps of the above super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy are as follows:
[0081] Accurately weigh the raw materials in the above proportions (magnesium ingots, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingots, zinc ingots, anhydrous manganese chloride, metallic strontium, and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate, and then fill with argon. Wait until the temperature rises to 725 ± 1 °C and melt for 50 min, then cool down to 670 ± 1 °C, stand for 20 min, and finally cast into a magnesium-lithium alloy cast rod.
[0082] The obtained magnesium-lithium alloy cast rod is subjected to homogenization heat treatment at 370 ± 1 °C for 6 h.
[0083] The homogenized magnesium-lithium alloy cast rod is subjected to hot extrusion. The extrusion parameters are as follows: the temperature of the cast rod is 230 ± 1 °C, the extrusion rate is 5.0 mm / s, and the extrusion ratio is 20:1. Finally, a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is obtained.
[0084] The performance testing method is the same as that in Example 1. In this example, the density of the super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is 1.45 g / cm 3 , the tensile strength is 321.45 MPa, the yield strength is 227.3 MPa, and the elongation is 23.1% (see Table 1 for details).
[0085] Example 4
[0086] This embodiment provides an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components in mass percentage: Li 12%, La 1.2%, Ce 1.1%, Al 4.3%, Zn 0.9%, Mn 0.25%, Sr 0.02%, Y 0.03%, Fe ≤ 0.05wt%, Ni ≤ 0.005wt% and Cu ≤ 0.05wt%, and the balance is Mg and unavoidable impurities.
[0087] The specific steps of the above ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy are as follows:
[0088] Accurately weigh the raw materials (magnesium ingots, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingots, zinc ingots, anhydrous manganese chloride, metallic strontium and Mg-Y 30 master alloy) according to the above ratio, add them into a vacuum melting furnace, then evacuate, and then fill with argon. Wait until the temperature rises to 720 ± 1 °C and melt for 50 min, then cool down to 670 ± 1 °C, stand for 17 min, and finally cast into magnesium-lithium alloy ingots.
[0089] Heat the as-cast magnesium-lithium alloy ingots obtained by melting at 365 ± 1 °C for 4.5 h for homogenization heat treatment.
[0090] Hot extrude the homogenized magnesium-lithium alloy ingots. The extrusion parameters are: the ingot temperature is 235 ± 1 °C, the extrusion rate is 3.5 mm / s, and the extrusion ratio is 20:1. Finally, an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy is obtained.
[0091] The performance test method is the same as that in Example 1. The density of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy in this embodiment is 1.42 g / cm 3 , the tensile strength is 333.72 MPa, the yield strength is 230.9 MPa, and the elongation is 25.4% (see Table 1 for details).
[0092] Example 5
[0093] This embodiment provides an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components in mass percentage: Li 13%, La 0.8%, Ce 1.8%, Al 6.2%, Zn 1.7%, Mn 0.2%, Sr 0.03%, Y 0.02%, Fe ≤ 0.05wt%, Ni ≤ 0.005wt% and Cu ≤ 0.05wt%, and the balance is Mg and unavoidable impurities.
[0094] The specific steps of the above ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy are as follows:
[0095] Accurately weigh the above-mentioned raw materials (magnesium ingots, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingots, zinc ingots, anhydrous manganese chloride, metallic strontium, and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate, and refill with argon. Wait until the temperature rises to 690 ± 1 °C and melt for �0 min, then cool to 670 ± 1 °C, stand for 17 min, and finally cast into a magnesium-lithium alloy ingot bar.
[0096] Keep the magnesium-lithium alloy ingot bar obtained from melting at 365 ± 1 °C for 4.5 h for homogenization heat treatment.
[0097] Perform hot extrusion on the homogenized magnesium-lithium alloy ingot bar. The extrusion parameters are: the ingot bar temperature is 235 ± 1 °C, the extrusion rate is 3.5 mm / s, and the extrusion ratio is 20:1. Finally, a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is obtained.
[0098] The performance test method is the same as that in Example 1. In this example, the density of the super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is 1.41 g / cm 3 , the tensile strength is 360.79 MPa, the yield strength is 260.5 MPa, and the elongation is 20.3% (see Table 1 for details).
[0099] Example 6
[0100] This example provides a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components in mass percentage: Li 14%, La 1.0%, Ce 2.1%, Al 5.8%, Zn 2.2%, Mn 0.2%, Sr 0.03%, Y 0.02%, Fe ≤ 0.05 wt%, Ni ≤ 0.005 wt%, and Cu ≤ 0.05 wt%. The balance is Mg and unavoidable impurities.
[0101] The specific steps of the above-mentioned super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy are as follows:
[0102] Accurately weigh the above-mentioned raw materials (magnesium ingots, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingots, zinc ingots, anhydrous manganese chloride, metallic strontium, and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate, and refill with argon. Wait until the temperature rises to 750 ± 1 °C and melt for 30 min, then cool to 670 ± 1 °C, stand for 17 min, and finally cast into a magnesium-lithium alloy ingot bar.
[0103] Keep the magnesium-lithium alloy ingot bar obtained from melting at 365 ± 1 °C for 4.5 h for homogenization heat treatment.
[0104] Perform hot extrusion on the homogenized magnesium-lithium alloy ingot bar. The extrusion parameters are: the ingot bar temperature is 235 ± 1 °C, the extrusion rate is 3.5 mm / s, and the extrusion ratio is 20:1. Finally, a super-light, high-strength, and high-plasticity deformed magnesium-lithium alloy is obtained.
[0105] The performance test method is the same as that in Example 1. In this example, the density of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy is 1.40 g / cm 3 , the tensile strength is 340.36 MPa, the yield strength is 235.3 MPa, and the elongation is 33.7% (see Table 1 for details).
[0106] Example 7
[0107] This example provides an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy, which is composed of the following components in mass percentage: Li 15%, La 1.5%, Ce 1.0%, Al 7.0%, Zn 2.0%, Mn 0.30%, Sr 0.02%, Y 0.04%, Fe ≤ 0.05 wt%, Ni ≤ 0.005 wt% and Cu ≤ 0.05 wt%, and the balance is Mg and unavoidable impurities.
[0108] The specific steps of the above ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy are as follows:
[0109] Accurately weigh the above raw materials (magnesium ingots, pure lithium, Mg-La 30 master alloy, Mg-Ce 30 master alloy, aluminum ingots, zinc ingots, anhydrous manganese chloride, metallic strontium and Mg-Y 30 master alloy), add them to a vacuum melting furnace, then evacuate, and then fill with argon. Wait until the temperature rises to 720 ± 1 °C and melt for 50 min, then cool to 670 ± 1 °C, stand for 17 min, and finally cast into a magnesium-lithium alloy ingot.
[0110] The obtained magnesium-lithium alloy ingot is subjected to homogenization heat treatment at 365 ± 1 °C for 4.5 h.
[0111] The homogenized magnesium-lithium alloy ingot is hot-extruded, and the extrusion parameters are: the temperature of the ingot is 235 ± 1 °C, the extrusion rate is 3.5 mm / s, and the extrusion ratio is 20:1. Finally, an ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy is obtained.
[0112] The performance test method is the same as that in Example 1. In this example, the density of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy is 1.38 g / cm 3 , the tensile strength is 343.74 MPa, the yield strength is 248.2 MPa, and the elongation is 34.6% (see Table 1 for details).
[0113] Comparative Example 1
[0114] This comparative example provides a deformed magnesium-lithium alloy, which is only different from that in Example 1 in that the Li content is 5 wt%.
[0115] The performance test method is the same as that in Example 1. In this comparative example, the density of the deformed magnesium-lithium alloy is 1.62 g / cm 3, the tensile strength is 241.11 MPa, the yield strength is 172.7 MPa, and the elongation is 12.9% (see Table 1 for details). This is because the decrease in the Li element content reduces the slip system in the crystal structure, weakens the ability to hinder dislocation movement, and to a certain extent reduces the strength and plasticity of the magnesium-lithium alloy.
[0116] Comparative Example 2
[0117] The difference from Example 1 is only that the magnesium-lithium alloy in this comparative example was not subjected to homogenization heat treatment.
[0118] The performance test method is the same as that of Example 1. The density of the magnesium-lithium alloy in this comparative example is 1.59 g / cm 3 , the tensile strength is 203.46 MPa, the yield strength is 126.6 MPa, and the elongation is 5.6% (see Table 1 for details). It may be due to the lack of homogenization heat treatment, resulting in composition segregation, large-sized grains and second phases, and possible defects such as undissolved brittle phases in the structure; when the magnesium-lithium alloy is subjected to external forces, problems such as local stress concentration occur, weakening the mechanical properties of the material.
[0119] Comparative Example 3
[0120] The difference from Example 4 is only that Li element was not added when preparing the alloy in this comparative example.
[0121] The performance test method is the same as that of Example 1. The density of the magnesium alloy obtained in this comparative example is 1.92 g / cm 3 , the tensile strength is 330.23 MPa, the yield strength is 212.3 MPa, and the elongation is 8.6% (see Table 1 for details). Without adding Li element in the magnesium alloy, its density increases significantly, and at the same time, the alloy loses the lightweight advantage and high plasticity characteristics of the low-density β phase.
[0122] Comparative Example 4
[0123] The difference from Example 4 is only that Al element was not added when preparing the magnesium-lithium alloy.
[0124] The performance test method is the same as that of Example 1. The density of the magnesium alloy obtained in this comparative example is 1.41 g / cm 3 , the tensile strength is 220.79 MPa, the yield strength is 155.2 MPa, and the elongation is 27.3% (see Table 1 for details). Without adding Al element in the magnesium-lithium alloy, it loses the solution strengthening and precipitation strengthening of Al element, and its strength decreases significantly.
[0125] Table 1 Density and mechanical properties of the alloy
[0126] <![CDATA[Density g / cm 3 > Tensile strength / MPa Yield strength / MPa Elongation / % Example 1 1.59 284.04 203.3 17.5 Example 2 1.58 316.13 212.7 18.7 Example 3 1.45 321.45 227.3 23.1 Example 4 1.42 333.72 230.9 25.4 Example 5 1.41 360.79 260.5 20.3 Example 6 1.40 340.36 235.3 33.7 Example 7 1.38 343.74 248.2 34.6 Comparative Example 1 1.62 241.11 172.7 12.9 Comparative Example 2 1.59 203.46 126.6 5.6 Comparative Example 3 1.92 330.23 212.3 8.6 1.41 220.79 155.2 27.3
[0127] As can be seen from Table 1, the present invention has successfully prepared a super-light, high-strength and high-plasticity deformed magnesium-lithium alloy with a density of 1.38 - 1.59 g / cm 3 , a tensile strength ≥ 284 MPa, a yield strength ≥ 203 MPa, and an elongation of 17 - 35%, meeting the stringent requirements of the aerospace, military, and 3C electronics fields for high-performance and lightweight materials, and providing strong support for the wide application of magnesium-lithium alloys.
[0128] The above is only the preferred specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.
Claims
1. A super-light, high-strength and high-plasticity deformed magnesium-lithium alloy, characterized in that, By mass percentage, it comprises the following components: Li 7.0 - 15.0%, La 0.01 - 1.8%, Ce 0.01 - 2.5%, Al 1.0 - 7.0%, Zn 0.5 - 3.0%, Mn 0.15 - 0.4%, Sr 0.01 - 0.05%, Y 0.01 - 0.05%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and inevitable impurities.
2. The ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 1, wherein By mass percentage, it comprises the following components: Li 11.0 - 15.0%, La 0.8 - 1.7%, Ce 1.0 - 2.1%, Al 4.3 - 7.0%, Zn 0.9 - 2.2%, Mn 0.2 - 0.4%, Sr 0.02 - 0.05%, Y 0.02 - 0.04%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and inevitable impurities.
3. The ultra-light, high-strength and high-plasticity-deformation magnesium-lithium alloy according to claim 2, characterized in that, By mass percentage, it comprises the following components: Li 12.0 - 15.0%, La 0.8 - 1.5%, Ce 1.0 - 2.1%, Al 4.3 - 7.0%, Zn 0.9 - 2.2%, Mn 0.2 - 0.3%, Sr 0.02 - 0.03%, Y 0.02 - 0.04%, Fe ≤ 0.05%, Ni ≤ 0.005%, and Cu ≤ 0.05%, with the balance being Mg and inevitable impurities.
4. A method for preparing the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to any one of claims 1 to 3, characterized in that, It includes the following steps: Weigh the raw materials by mass percentage, then melt the raw materials, and after the melting is completed, carry out casting to obtain a magnesium - lithium alloy ingot; successively carry out homogenization heat treatment and hot extrusion on the magnesium - lithium alloy ingot to obtain the ultra - light, high - strength and high - plasticity deformed magnesium - lithium alloy. The temperature of the melting is 690 - 750 °C, and the time of the melting is 30 - 60 min.
5. The preparation method of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 4, characterized in that The raw materials include pure lithium, pure magnesium, magnesium - lanthanum master alloy, magnesium - cerium master alloy, pure aluminum, pure zinc, anhydrous manganese chloride, metallic strontium, and magnesium - yttrium master alloy.
6. The preparation method of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 4, characterized in that, After the melting is completed, cool down and stand still before carrying out casting.
7. The preparation method of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 6, characterized in that, The cooling and standing still means cooling to a temperature of 670 ± 1 °C and standing still for 10 - 20 min.
8. The preparation method of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 4, characterized in that, The temperature of the homogenization heat treatment is 350 - 380 °C, and the time of the homogenization heat treatment is 4 - 6 h.
9. The preparation method of the ultra-light, high-strength and high-plasticity deformed magnesium-lithium alloy according to claim 4, characterized in that, During the hot extrusion: the temperature of the ingot is 210 - 250 °C, the extrusion rate is 3.0 - 5.0 mm / s, and the extrusion ratio is 20∶1.
10. Application of the ultra - light, high - strength and high - plasticity deformed magnesium - lithium alloy according to any one of claims 1 - 3 in the fields of 3C electronics, military equipment or aerospace.